Particulate Phosphorus in the Everglades Agricultural Area: I -- Introduction and Sources - Samira H. Daroub; James D. Stuck; Timothy A. Lang; Orlando A. Diaz (EDIS, 2002)
This document is SL 197, one of a series of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published September 2002. This publication is also a part of the Florida Sugarcane Handbook, an electronic publication of the Agronomy Department.